AKUNTAN DI ERA DIGITAL: PENDEKATAN TAM (TECHNOLOGY ACCEPTANCE MODEL) PADA SOFTWARE BERBASIS AKUNTANSI ACCURATE ONLINE - RASMON RASMON (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This research is a quantitative research that aims to determine the acceptance and use of Accurate Oline with the Technology Acceptance Model approach. Sampling used a random sampling method with a total sample of 27 alumni practitioners of the Accurate Online Program LKP Sahabat Prestasi who have worked in companies throughout Indonesia. The hypothesis testing in this study used SPSS Version 25. The test results showed that (1) the ability to use a computer affects perceived usefulness, (2) the ability to use a computer affects perceived ease of use, (3) perceived ease of use affects perceived usability, (4) perceived usefulness influences user attitudes, (5) perceived ease of use influences user attitudes. This research is expected to open minds that the use of technology is very important in the current era where business transactions are increasingly complicated.